2014
DOI: 10.1007/s10539-014-9450-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Wright’s (1932) adaptive field to contemporary interpretations and uses of fitness landscapes in the social sciences

Abstract: The working paper features an extended literature overview of the ways in which fitness landscapes have been interpreted and used in the social sciences, for which there was not enough space in the full article. The article features an in-depth philosophical discussion about the added value of the various ways in which fitness landscapes are used in the social sciences. This discussion is absent in the current working paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…The second-generation models developed by Balietti et al (2015) and Currie and Avin (2019) provide another kind of example, where the models as well as the argumentative goals and the conceptual premises are quite different. Just as Weisberg and Muldoon borrowed their argumentative device (the idea of an adaptive landscape and the techniques to model it) from biology and adapted it to serve their own purposes (Gerrits and Marks 2015), these authors transform the EL framework to suit their purposes. As in the case of Balietti et al, the audiences can be remarkably different too.…”
Section: Modelling Moves Include (But Are Not Limited To)mentioning
confidence: 99%
“…The second-generation models developed by Balietti et al (2015) and Currie and Avin (2019) provide another kind of example, where the models as well as the argumentative goals and the conceptual premises are quite different. Just as Weisberg and Muldoon borrowed their argumentative device (the idea of an adaptive landscape and the techniques to model it) from biology and adapted it to serve their own purposes (Gerrits and Marks 2015), these authors transform the EL framework to suit their purposes. As in the case of Balietti et al, the audiences can be remarkably different too.…”
Section: Modelling Moves Include (But Are Not Limited To)mentioning
confidence: 99%
“…Evolutionary spaces have been deployed in other contexts. For example, fitness landscapes and particularly the Kauffman–Levin N–K landscapes spread to the social sciences (reviewed in [ 3 , 63 ]). Raup's theoretical morphospace and general principles of network architecture were used to generate a network morphospace spanning food webs to neural and electrical circuits [ 64 ].…”
Section: Evolutionary Spaces: a Bestiarymentioning
confidence: 99%
“…Waddington's introduction of the epigenetic landscape extended Wright's metaphor to development [ 2 ]. Evolutionary spaces have also been adopted in social sciences, including economics [ 3 ]. In some cases, the relationship between spaces has received considerable attention, as with genotype–phenotype mapping in small RNAs [ 4 , 5 ] and in empirical studies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gerrits et al (2014), Barkley Rosser Jr (1999, 2012. In Frenken (2001) and Frenken and Valente (2004) the authors, following Kaufmann's NK model theory, suggested a formalisation of network organisations in searching a complex fitness landscape of technological artefacts and innovations characterised by conflicting constraints due to interdependencies between its constituting elements.…”
Section: Nk Model and Economic Complex Systemsmentioning
confidence: 99%